Linkage relationship of isozyme loci in diploid taro Colocasia esculenta (L.) Schott - Viet, Nguyen Xuan (Academia Journal of Biology, 2015)
Linkage relationship of isozyme loci in diploid taro Colocasia esculenta (L.) Schott